Endurance training attenuates doxorubicin-induced cardiac oxidative damage in mice - A. Ascensão (2005)
Background: There is a lack of studies reporting the influence of DOX treatment on chronically exercised animals. This study intended to determine the effect of endurance swimming training on cardiac muscle tolerance to in vivo DOX-induced damage, analyzing the levels of oxidative stress markers, the response of antioxidant system and the expression of 60 and 70 kDa heat shock proteins (HSP). Methods: Forty-four Charles River CD1 male mice were randomly assigned to either non-trained placebo (NT+P) and non-trained DOX (NT+DOX) or trained placebo (T+P) and trained DOX (T+DOX). Twenty-four hours after completion of a 14-week training, cardiac ventricles were extracted for biochemical assays of oxidative stress and damage markers, antioxidant enzymes and HSPs. Results: DOX treatment per se (single 20 mg kg(-1) dose), administrated 24 h after the last exercise bout, elevated (p < 0.05) plasma cardiac troponin I (cTnl), HSP60, % oxidized glutathione, thiobarbituric acid reactive substances and carbonyl groups and reduced -SH groups. However, training induced a significant increase (p < 0.05) on total and reduced glutathione (GSH), HSP60 expression, and decreased the rise of plasma cTnI as well as cardiac carbonyl groups contents in DOX hearts, when compared to NT+DOX mice. Although catalase activity of T+DOX was significantly higher than T+P, no changes were observed in the activities of superoxide dismutase, glutathione peroxidase and glutathione reductase. Neither DOX nor training induced significant variations in HSP70. Conclusion: Training improved myocardial tolerance to DOX-induced damage. It is likely that the improvement in responses to DOX was related to training-induced increases in GSH and HSP60.